Optimizing Initial Intrathecal Drug Ratio for Refractory Cancer-Related Pain for Early Pain Relief. A Retrospective Monocentric Study. Issue 10 (7th May 2019) - Dupoiron, Denis; Leblanc, Damien; Demelliez-Merceron, Sybille; Bore, Francois; Seegers, Valerie; Dubois, Pierre Yves; Pechard, Marie; Robard, Serge; Delorme, Thierry; Jubier-Hamon, Sabrina; Carvajal, Gabriel; Lebrec, Nathalie
Abstract: Objective: Intrathecal (IT) drug delivery has shown its efficiency in treating refractory cancer pain, but switching opioids from the systemic to the intrathecal route is a challenging phase. Moreover, associations are widely used and recommended. Few data deal with the initial dosage of each drug. Analyzing conversion factors and initial dosages used in intrathecal therapy seems essential to decreasing the length of titration and to delivering quick pain relief to patients. Methods: We retrospectively analyzed data from consecutive adult patients implanted with an intrathecal device for cancer pain and treated at the Institut de Cancérologie de l'Ouest, in Angers, France, for four years. The main goal was to identify factors associated with early pain relief after intrathecal drug delivery system (IDDS) implantation. Results: Of the 220 IDDS-treated patients, 70 (32%) experienced early pain relief (EaPR) and 150 (68%) delayed pain relief (DePR). Performance Status stage and initial IT ropivacaine:IT morphine ratio were the variables independently associated with EaPR. The best IT ropivacaine:IT morphine ratio to predict EaPR was 5:1, with a 73% (95% confidence interval [CI] = 64.8% to 79.6%) sensitivity and a 67.1% (95% CI = 54.9% to 77.9%) specificity. EaPR subjects experienced better pain relief (–84% vs –60% from baseline pain score, P < 0.0001), shorter length of hospitalization (7 vs 10 days, P < 0.0001), and longer survival (155 vs 82 days, P = 0.004). Conclusions: Local anesthetic:morphine ratio should be considered when starting IDDS treatment. EaPR during the IT analgesia titration phase was associated with better pain relief and outcomes in patients with refractory cancer-related pain.